TINJAUAN PUSTAKA: PERAN SEKOLAH ISLAM DALAM MEMBENTUK KESADARAN POLITIK DAN KEWARGANEGARAAN SISWA - Fitria, Lailatul; Ali, Irfan; Putriana, Eka; Khairul Anam, Rifqi (As-Sulthan Journal of Education, 2026)
Islamic schools play a strategic role in shaping students’ political and civic awareness amid the increasingly complex socio-political dynamics of Indonesian society. This article aims to systematically examine the role of Islamic schools in cultivating students’ political awareness and civic identity based on findings from previous studies. The method employed is a literature review, analyzing various scholarly sources, including books, journal articles, and policy documents related to Islamic education, civic education, and political education. The findings indicate that Islamic schools contribute significantly through the integration of the national curriculum with Islamic values, particularly within Civic and Pancasila Education, Islamic Religious Education, as well as extracurricular activities and school culture. Islamic values such as justice (al-‘adl), trust (amanah), deliberation (shura), responsibility, tolerance, and social concern serve as ethical foundations in shaping students’ moderate and democratic political attitudes. Moreover, teachers’ roles as role models, participatory school environments, and students’ involvement in school organizations further strengthen the formation of civic awareness. Nevertheless, the review also identifies several challenges, including limited teacher competence, insufficient curriculum integration, and the influence of globalization. Therefore, strengthening political education grounded in Islamic values is essential to developing a generation of Muslims with strong character, political awareness, and responsibility within democratic life.